2005
DOI: 10.4012/dmj.24.134
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Diamond Burs for the Fabrication of Ceramic Crowns Using Dental CAD/CAM

Abstract: The diamond burs of two dental CAD/CAM systems (GN and CD) were examined if they could be used to fabricate up to 21 ceramic full crowns without fracture.After one, 11, and 21 machining times, the surfaces of the diamond burs were observed and the number of particles captured on SEM pictures was counted.The average surface roughness of the crowns was also measured.All diamond burs could be used to fabricate 21 ceramic crowns without fracture. A significant decrease in the number of diamond particles was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 8 publications
4
26
1
Order By: Relevance
“…In particular, the porcelain firing cycle can cause a negative effect on the marginal fit of all-ceramic crowns 3) , and hence the success of the restorations 4,5) . All-ceramic crowns can be fabricated using two types of computer-aided design/computer-aided manufacturing (CAD/CAM) systems [6][7][8] : a doublelayer type which has a high-strength core, and a single-layer type without core (the entire crown is fabricated by a CAD/CAM system). The addition of porcelain to the copings of double-layer type may cause a negative effect on the fit of the crowns 3,9) .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the porcelain firing cycle can cause a negative effect on the marginal fit of all-ceramic crowns 3) , and hence the success of the restorations 4,5) . All-ceramic crowns can be fabricated using two types of computer-aided design/computer-aided manufacturing (CAD/CAM) systems [6][7][8] : a doublelayer type which has a high-strength core, and a single-layer type without core (the entire crown is fabricated by a CAD/CAM system). The addition of porcelain to the copings of double-layer type may cause a negative effect on the fit of the crowns 3,9) .…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the great majority of the milled frameworks presented a smooth surface (Figure 4-a). Some rougher surfaces probably due to the excess number of frameworks milled with the same bur 8 were discarded (Figure 4-b).…”
Section: Resultsmentioning
confidence: 99%
“…When used for frameworks, this material is usually sintered into a block and the completely sintered block is milled mechanically using a CAD/CAM system. However, this method presents some problems, such as the setup and operating costs of the CAD/CAM system and premature wear of the cutting tool 11) . Furthermore, it has been reported that when subjected to milling, even high-strength zirconia-based materials are often reduced in strength 12) or that the process may generate microcracks 13) .…”
Section: Discussionmentioning
confidence: 99%